Validation of post‐traumatic growth inventory in mothers with the experience of having the NICU‐Hospitalized newborns "validation of post‐traumatic growth inventory" - Nahid Bayrami; Maryam Rassouli; Azam Shirinabadi Farahani; Mehdi Heidarzadeh; Fatemeh Khademi; Salehe Tajlli; Mohadese Babaie; Anahita Masoum poor; Khadijeh Hatamipour (Wiley, 2023)
Abstract Aims Investigating post‐traumatic growth (PTG) in mothers with the experience of having a preterm newborn hospitalized in the NICU requires a valid tool. This study aims to determine the validity and reliability of the Farsi version of the post‐traumatic growth inventory (PTGI) in mothers with the experience of having their newborns hospitalized in the NICU. Design This study was methodological research. Methods In this study, 250 mothers who had newborns with a history of NICU hospitalization during the last 3 to 12 months and had visited paediatric clinics of the selected hospitals in Tehran with the aim of having their children's condition examined were selected through convenience sampling. The data were collected using a demographic information questionnaire and PTGI. The face validity, the construct validity (confirmatory factor analysis), and the internal consistency reliability of the inventory were measured using SPSS V22 and LISREL V8.8. Results According to appropriate values for factor analysis fit indices (FI = 0.94, RMSEA = 0.07, IFI = 0.94, NFI = 0.93, RFI = 0.91, NNFI = 0.93, SRMR = 0.07), 21 items and 5 factors were confirmed for this inventory. Furthermore, Cronbach's alpha coefficient of this inventory was measured as α = 0.94. Conclusion According to favourable psychometric properties, the Farsi version of PTGI is a suitable tool for studying PTG in mothers with the experience of having preterm newborns in the NICU. Using PTGI can help nurses in planning family‐centered care interventions to reduce the impact of the mental trauma caused by the preterm newborn's hospitalization in parents. Patient or Public Contribution Mothers who had newborns with a history of NICU hospitalization during the last 3-12 months.